PEMURIDAN SEBAGAI UPAYA MENANAMKAN IMAN KEPADA KRISTUS PADA MAHASISWA STAK TERPADU PESAT SALATIGA - Melben Nainupu; Ahmad Tabrani; Frets Keriapy (Vox Dei: Jurnal Teologi dan Pastoral, 2020)
The development of science and technology is so fast that it can affect the social life of both individuals and groups. Humans are faced with diverse lifestyles and a lifestyle crisis is a serious condition in today's post-modern era. Therefore it is very important for believers to be discipled so that they have the character of Christ which influences their socialization. Seeing the existing problems, the purpose of this study is to describe discipleship as an effort to instill faith in students of the PESAT Integrated STAK Salatiga in their belief in Christ. The method used in this research is qualitative. Data collection through observation and interviews and data analysis techniques include field notes, reduction, display, and conclusions. All respondents can understand and participate in the process of discipleship that takes place by exemplifying life by followers of Christ. From the research results, it was found that discipleship with the mentoring process carried out by STAK Terpadu Pesat could instill students' faith in Christ.